A novel botanical formula improves eye fatigue and dry eye: a randomized, double-blind, placebo-controlled study. Issue 2 (15th June 2020) - Kan, Juntao; Wang, Min; Liu, Ying; Liu, Hongyue; Chen, Liang; Zhang, Xue; Huang, Chengrong; Liu, Bryan Y; Gu, Zhensheng; Du, Jun
ABSTRACT: Background: With the frequent use of video display units, eye fatigue is becoming more common globally. An alternative nutritional strategy is needed to prevent the aggravation of eye fatigue symptoms. Objectives: The objective was to evaluate the protective effect of a novel botanical combination of lutein ester, zeaxanthin, and extracts of blackcurrant, chrysanthemum, and goji berry on adults with eye fatigue in a randomized, double-blind, placebo-controlled clinical trial. Methods: We randomly allocated 360 participants into 4 groups to receive placebo and 3 doses of our formula (chewable tablets, containing 6 mg, 10 mg, or 14 mg of lutein) once daily for 90 d. Each participant had 3 visits at baseline (V1), 45 d (V2), and 90 d (V3) during the study. Results: Intervention with the formula improved individual scores of eye fatigue symptoms, including eye soreness, blurred vision, dry eye, foreign body sensation, and tearing. Compared with placebo, the formula at all 3 doses significantly decreased the total score of eye fatigue symptoms and increased the visuognosis persistence time at both V2 and V3. According to the Schirmer test, both 10-mg and 14-mg lutein formula groups had improved tear secretion at V3 compared with the placebo. The keratography results indicated that the first tear break-up time, average tear break-up time, and tear meniscus height were significantly increased after formula intervention. The formula at all 3 doses significantly increased the macular pigment optical density at V2 and V3 compared with the placebo, whereas optical coherence tomography showed no significant difference in retinal thickness and retinal volume across all groups at both visits. Conclusions: Our botanical formula improves eye fatigue, dry eye, and macular function without changing the retinal structure, and thus it could serve as an effective nutritional strategy in improving eye fatigue without causing serious side effects. Clinical Trial Registry: chictr.org.cn (ChiCTR1800018987).